TINJAUAN SISTEM INFORMASI PENGUPAHAN KARYAWAN PADA PT. X - Bokings, T. P. O Riska; Putri, Novy Cintya Mustika (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2022)
The wage information system is an important component in accounting information. This system consists of an interconnected framework within a company that serves to inform cost data required by interested parties within the company. With this, the author makes a final project entitled Overview of Employee Wage Information Systems at PT. X aims to determine the employee wage information system at PT. X. This type of research uses a descriptive qualitative research method, which focuses on the employee wage information system at PT. X. Data collection techniques from this study using interview, observation, documentation, and literature study techniques. The review of the data in this study begins with the components of the wage information system consisting of related functions/organizational units, documents used, accounting records used, procedures that make up the system, elements of the internal control system, and flowcharts. The results of the study found evidence that the Wage Information System at PT. X has been carried out quite well, but several procedures have not been carried out/not following the Wage Information System, namely validation of salary slips from the finance department because validation is only done after printing the salary slips that are submitted and archived in the Personnel section. Good practice applied to support internal control is the payment of employee wages by transferring wages to each employee's account and making double payslips.